Substance use disorders among adults who are deaf or hard of hearing in the United States. (1st November 2021) - Park, Daejun; Lee, Othelia E.; Park, Junghyun; Minnick, Dane
Abstract: Background : There has been limited research on substance use disorders (SUDs) among individuals who are deaf or hard of hearing (DHH). This study explored associations among activities of daily living, instrumental activities of daily living, major depressive episode, risk perceptions for substance use, religiosity, and past-year SUDs within the DHH population. Methods : Data was drawn from the 2015–2019 National Survey on Drug Use and Health (N = 214, 505) to compare rates of past-year SUDs between DHH (weighted % = 5.4) and non-DHH populations. SUD measures included were past-year alcohol, marijuana, pain reliever, and illicit drug use disorders. Results : SUDs are more prevalent among the DHH population than the non-DHH population. When adjusted for sociodemographic variables, DHH adults were more likely to report experiencing all four types of measured SUDs. Significant associations were also found between all four measured SUDs and disability status, major depressive episodes, and perception of risk. An association between regular religious service attendance and alcohol, marijuana, or illicit drug use disorders was also identified, as well as an association between peer religiosity and marijuana use disorders. Conclusion : Given the high prevalence of SUDs and limited understanding of the mechanisms associated with the SUDs within the DHH population, more research is needed to address these issues. Highlights: SUDs are more prevalent among the DHH population than the non-DHH population. Religion and risk-perception are associated with decreased odds of SUDs in the DHH population. ADL, IADL, and MDE are associated with increased odds of SUDs in the DHH population.